2023
DOI: 10.3389/fneur.2023.1222574
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disease modifying therapies on cognitive functions typically impaired in multiple sclerosis patients: a clinician’s review

Abstract: ObjectiveOver the last few decades clinicians have become aware that cognitive impairment might be a major cause of disability, loss of employment and poor quality of life in patients suffering from multiple sclerosis [MS].The impact of disease modifying therapies [DMTs] on cognition is still a matter of debate. Theoretically, DMTs could exert a substantial beneficial effect by means of reducing neuroinflammation and brain atrophy, which are established correlates of cognitive dysfunction. The aim of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…In more recent trials, follow-up was only 1-2 years short, and thus insufficient to study long-term effects. Limitations regarding the cognitive tests and the small cohorts are also frequently reported [70]. Despite the previously mentioned impediments, a very recent review showed that most DMTs correlate with improved cognitive function [70].…”
Section: The Impact Of Medication and Cognitive Rehabilitation On Cog...mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent trials, follow-up was only 1-2 years short, and thus insufficient to study long-term effects. Limitations regarding the cognitive tests and the small cohorts are also frequently reported [70]. Despite the previously mentioned impediments, a very recent review showed that most DMTs correlate with improved cognitive function [70].…”
Section: The Impact Of Medication and Cognitive Rehabilitation On Cog...mentioning
confidence: 99%
“…Limitations regarding the cognitive tests and the small cohorts are also frequently reported [70]. Despite the previously mentioned impediments, a very recent review showed that most DMTs correlate with improved cognitive function [70]. The only two DMTs that showed inconsistent results were glatiramer acetate and fingolimod [71], but extensive real-world studies should be conducted.…”
Section: The Impact Of Medication and Cognitive Rehabilitation On Cog...mentioning
confidence: 99%
“…The introduction of effective disease-modifying therapies (DMTs) has markedly reduced the annual relapse rate and radiological progression. Moreover, DMTs also seem to have an impact on reducing the rate of cognitive impairment (CI) and the potential for improving cognitive parameters [5].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors associated with the development of CI in MS include older age, greater disability in EDSS scale [6], brain atrophy [7], fewer years of education, and male sex [8], although the data differs despite the studies. Factors that have a protective effect on the development of CI are DMTs [5] and the cognitive reserve [9]. There is little data on biochemical factors as predictors of CI in MS, studies having focused mainly on light neurofilaments, with contradictory results [10,11].…”
Section: Introductionmentioning
confidence: 99%